Subsurface drainage enhances the cadmium enrichment efficiency of flax-sesame crop rotation by inhibiting the immobilization effect of iron oxides - Changrong Wang; Ying Shang; Zhaoqinghua Wu; Weijie Xue; Yongchun Huang; Yuebing Sun; Zhongqi Liu (Ecotoxicology and Environmental Safety)
Flax-sesame crop rotation is an effective phytoremediation method for cadmium (Cd)-contaminated farmland. To investigate the effect of drainage on the uptake efficiency of soil Cd by the crops, field experiments were conducted to analyze the migration of Cd, iron (Fe), and manganese (Mn), and the soil microbial community. Compared with conventional drainage, the deep furrow treatment increased the Cd2 + accumulated in the flax and sesame organs by up to 73.9 % and decreased the soil Cd2+ content by 4.7 %-7.7 %. The accumulation of Fe2+/Fe3+ and Mn2+ showed the same trend as that of Cd. In the soil, deep furrow drainage increased the bioavailability of Cd2+, Mn2+ and Fe2+/Fe3+, while decreased the content of Fe-Mn oxide-bound Cd2+ and that of amorphous Fe2+/Fe3+ oxide by up to 13.3 %, indicating that changes in Fe morphology was highly related with the Cd availability. Further sequencing of the soil microbial community found that deep furrow drainage increased the relative abundance of Fe-redox bacteria Acidobacteria, Comamonas, Flavobacterium, Saccharimonadales, and Novosphingobium by up to 45.8 %, 63.7 %, 1204.1 %, 61.2 % and 93.5 % at the mature stage, respectively. And the relative abundance of other siderophore-secreting bacteria, including Lysobacter and Burkholderiales, increased by up to 85.2 % and 41.6 %, respectively. These findings indicated that the activation of key Fe-associated bacteria facilitated ferrolysis, playing a crucial role in enhancing Fe bioavailability and mitigating the immobilization effect of Fe2+/Fe3+ oxides on Cd2+ in soil. The implementation of deep furrow drainage significantly increased soil Cd2+ availability and enhanced Cd2+ uptake efficiency in the flax-sesame rotation system.